2020
DOI: 10.1029/2019wr026153
|View full text |Cite
|
Sign up to set email alerts
|

The Added Value of Different Data Types for Calibrating and Testing a Hydrologic Model in a Small Catchment

Abstract: This study investigated the added value of different data for calibrating a runoff model for small basins. The analysis was performed in the 66 ha Hydrological Open Air Laboratory, in Austria. An Hydrologiska Byråns Vattenbalansavdelning (HBV) type, spatially lumped hydrologic model was parameterized following two approaches. First, the model was calibrated using only runoff data. Second, a step-by-step approach was followed, where the modules of the model (snow, soil moisture, and runoff generation) were cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 74 publications
(126 reference statements)
2
23
0
2
Order By: Relevance
“…Since the curve number (CN2) was the most sensitive parameter for streamflow, these results suggest that adjusting CN2 value is sufficient to obtain a good flow calibration for the HOAL catchment. These results are similar to Széles et al [36] who applied the Hydrologiska Byråns Vattenbalansavdelning (HBV) model [81] in the HOAL catchment. They noted that the model was able to produce very good streamflow results after runoff calibration, whereby their model obtained a logarithmic NSE value of 0.81.…”
Section: Effect Of Calibration Steps On Hydrological Componentssupporting
confidence: 88%
See 2 more Smart Citations
“…Since the curve number (CN2) was the most sensitive parameter for streamflow, these results suggest that adjusting CN2 value is sufficient to obtain a good flow calibration for the HOAL catchment. These results are similar to Széles et al [36] who applied the Hydrologiska Byråns Vattenbalansavdelning (HBV) model [81] in the HOAL catchment. They noted that the model was able to produce very good streamflow results after runoff calibration, whereby their model obtained a logarithmic NSE value of 0.81.…”
Section: Effect Of Calibration Steps On Hydrological Componentssupporting
confidence: 88%
“…Highquality soil data used during model set-up in our study can, therefore, be attributed to the good soil moisture simulation and, therefore, the negligible impact of soil moisture calibration on streamflow. Széles et al [36] also did not report any significant improvement in streamflow prediction for the HOAL catchment after incorporating soil moisture data in their research; however, they reported an improved soil moisture prediction by the model. Rajib et al [34] used in-situ soil moisture estimates for top 60 cm of soil profile in their multi-objective approach and reported an improvement of R 2 from 0.69 to 0.72 in streamflow calibration after soil moisture calibration.…”
Section: Effect Of Calibration Steps On Hydrological Componentsmentioning
confidence: 79%
See 1 more Smart Citation
“…These models, however, are very sensitive to many input and parameters [6] and their applicability at large scales can be limited by the availability of input data and parameters and their accuracy [7]. For these reasons, several studies aimed to improve model performances by integrating new observations [8], calibrating the model in comparison to independent data and based on different objective functions [9] or by data assimilation techniques [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays many satellite products are in fact free available in almost real time (within a few hours from the acquisition time), and they can be quickly integrated for improving model prediction [12]. In this context, it becomes very important to assess which input and parameters might be more relevant for improving the performance of the model and to prioritize data collection and model integration [8], [13], [14].…”
Section: Introductionmentioning
confidence: 99%